Mrs. McGinty's dead - Christie, Agatha, 1890-1976. (New York : HarperPaperbacks, 1980)
When a man is sentenced to death for the brutal murder of his landlord, Superintendent Spence, convinced of the man's innocence, seeks the help of former-police officer Hercule Poirot in solving the mystery.
Wilson's Fiction.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction